Gene Expression Profiling Reveals Renin mRNA Overexpression in Human Hypertensive Kidneys and a Role for MicroRNAs - Marques, Francine Z.; Campain, Anna E.; Tomaszewski, Maciej; Zukowska-Szczechowska, Ewa; Yang, Yee Hwa J.; Charchar, Fadi J.; Morris, Brian J. (Hypertension (Dallas, Tex. 1979), 2011)
The kidney has long been invoked in the etiology of essential hypertension. This could involve alterations in expression of specific genes and microRNAs (miRNAs). The aim of the present study was to identify, at the transcriptome-wide level, mRNAs and miRNAs that were differentially expressed between kidneys of 15 untreated hypertensive and 7 normotensive white male subjects of white European ancestry. By microarray technology we found 14 genes and 11 miRNAs that were differentially expressed in the medulla. We then selected and confirmed by real-time quantitative PCR expression differences for NR4A1, NR4A2, NR4A3, PER1, and SIK1 mRNAs and for the miRNAs hsa-miR-638 and hsa-let-7c. Luciferase reporter gene experiments in human kidney (HEK293) cells confirmed the predicted binding of hsa-let-7c to the 3′ untranslated region of NR4A2 mRNA. In the renal cortex we found differential expression of 46 genes and 13 miRNAs. We then confirmed expression differences for AIFM1, AMBP, APOE, CD36, EFNB1, NDUFAF1, PRDX5, REN, RENBP, SLC13A1, STX4, and TNNT2 mRNAs and for miRNAs hsa-miR-21, hsa-miR-126, hsa-miR-181a, hsa-miR-196a, hsa-miR-451, hsa-miR-638, and hsa-miR-663. Functional experiments in HEK293 cells demonstrated that hsa-miR-663 can bind to the REN and APOE 3′ untranslated regions and can regulate REN and APOE mRNA levels, whereas hsa-miR-181a regulated REN and AIFM1 mRNA. Our data demonstrated for the first time that miRNAs can regulate renin expression. The observed downregulation of 2 miRNAs in hypertension could explain the elevation in intrarenal renin mRNA. Renin, CD36, and other mRNAs, as well as miRNAs and associated pathways identified in the present study, provide novel insights into hypertension etiology.